Motivación personal y desarrollo de convicciones como estrategia para lograr el éxito académico y personal en los estudiantes del séptimo año de educación básica paralelo A y B de la escuela fiscal mixta Juan Montalvo de la ciudad de Pasaje, periodo, 2013-2014. - Muñoz Quinde, Carlos Bismarck (2015)
The present research on personal motivation and development of convictions as a strategy to achieve academic and personal success considers aspects of particular importance in educational practice and constitute important factors to achieve personal development during the process of learning.